Analysis of Corporate Financial Performance Before and After Acquisition - Muslim, Muslim (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to determine differences in the company's financial performance before and after making acquisitions of non-financial companies listed on the Indonesia Stock Exchange (IDX), which are proxied by financial ratios Current Ratio (CR), Quick Ratio (QR), Cash Ratio ( Cr), Debt to Total Assets (DAR), Debt to Equity Ratio (DER), Earnings per Share (EPS), Price Earnings Ratio (PER), Return on Assets (ROA), and Return on Equity (ROE). The study population included all manufacturing companies, especially the primary and chemical industry sectors listed on the Indonesia Stock Exchange, which performed acquisition activities in 2013 – 2019, totaling 39 companies. The sample selection technique used a purposive sampling method, and five companies were obtained. The data analysis method used in this study includes the normality test and the paired sample t-test. The normality test was conducted to see whether the data is usually distributed. If the data is normally distributed, the paired sample t-test is used, but if the data is not normally distributed, then Wilcoxon's signed ranks test is used. The data analysis method used in this study is the paired sample t-test. The results of this study indicate that all research variables, namely, Current Ratio (CR), Quick Ratio (QR), Cash Ratio (Cr), Debt to Total Assets (DAR), Debt to Equity Ratio (DER), Earnings per Share (EPS), Price Earnings Ratio (PER), Return on Assets (ROA), and Return on Equity (ROE) did not experience significant changes three years after the acquisition.